2016
DOI: 10.1192/pb.bp.115.052472
|View full text |Cite
|
Sign up to set email alerts
|

Long-term antidepressant treatment in general practice: changes in body mass index

Abstract: Aims and method To discern changes in body mass index (BMI) in patients on long-term antidepressant treatment in a general practice population and establish BMI changes in patients with and without a diagnosis of diabetes. We used a retrospective observational method and identified patients on four antidepressants of interest. We excluded those who did not have start and current BMI readings within the past 3 years and noted whether or not patients had a diagnosis of diabetes.Results Long-term treatment with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This contrasts with previous research indicating that long-term treatment with citalopram, fluoxetine, mirtazapine and sertraline was associated with increased BMI. 18 This could be attributed to the grouping of various antidepressants or recall bias, as participants might have misreported the duration of their antidepressant use. It should be noted that there are additional factors, such as the lifetime duration of antidepressant use, that were not captured in the NHANES data, which may have also influenced the observed outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with previous research indicating that long-term treatment with citalopram, fluoxetine, mirtazapine and sertraline was associated with increased BMI. 18 This could be attributed to the grouping of various antidepressants or recall bias, as participants might have misreported the duration of their antidepressant use. It should be noted that there are additional factors, such as the lifetime duration of antidepressant use, that were not captured in the NHANES data, which may have also influenced the observed outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 15 A UK study analysed data for 268 patients treated with antidepressants from a general practice with 11 994 registered patients, and concluded that weight gain persisted during long term treatment, with, in some instances, prescriptions maintained for several years. 16 Another US study evaluated weight gain in the 12 months after initiation of antidepressant treatment in 22 610 adults treated in clinics in New England and found differences in the propensity of individual antidepressants to result in weight gain. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no guidelines but there are several recent studies and reviews that contain clinically relevant information on the difference in response to certain AD in patients with obesity and with certain obesity classes (5,53,72,73). There are also published detailed recommendations on how to avoid the weight-increasing effect of AD (11,22,54,(74)(75)(76)(77)(78)(79)(80). Of note, it has been shown in a recent RCT that patients with morbid obesity may benefit from certain AD and AD combinations (5,53) and, therefore, require individualized approach to treatment.…”
Section: Discussionmentioning
confidence: 99%